Genetic diversification of Panstrongylus geniculatus (Reduviidae: Triatominae) in northern South America (2019)
Triatomines are the vectors of Trypanosoma cruzi, the etiological agent of Chagas disease. Although Triatoma and Rhodnius are the most-studied vector genera, other triatomines, such as Panstrongylus, also transmit T. cruzi, creating new epidemiological scenarios. Panstrongylus has at least 13 reported species but there is limited information about its intraspecific genetic variation and patterns of diversification. Here, we begin to fill this gap by studying populations of P. geniculatus from Colombia and Venezuela and including other epidemiologically important species from the region. We examined the pattern of diversification of P. geniculatus in Colombia using mitochondrial and nuclear ribosomal data. Genetic diversity and differentiation were calculated within and among populations of P. geniculatus. Moreover, we constructed maximum likelihood and Bayesian inference phylogenies and haplotype networks using P. geniculatus and other species from the genus (P. megistus, P. lignarius, P. lutzi, P. tupynambai, P. chinai, P. rufotuberculatus and P. howardi). Using a coalescence framework, we also dated the P. geniculatus lineages. The total evidence tree showed that P. geniculatus is a monophyletic species, with four clades that are concordant with its geographic distribution and are partly explained by the Andes orogeny. However, other factors, including anthropogenic and eco-epidemiological effects must be investigated to explain the existence of recent geographic P. geniculatus lineages. The epidemiological dynamics in structured vector populations, such as those found here, warrant further investigation. Extending our knowledge of P. geniculatus is necessary for the accurate development of effective strategies for the control of Chagas disease vectors. © 2019 Caicedo-Garzón et al.